12. \( \left\{\begin{array}{l}4 x-y=-4 \\ 5 x=2 y+1\end{array}\right. \)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To solve the system of equations, we can rearrange the first equation for \( y \): From \( 4x - y = -4 \), we get \( y = 4x + 4 \). Now, we can substitute this expression for \( y \) into the second equation: \( 5x = 2(4x + 4) + 1 \). Simplifying gives us \( 5x = 8x + 8 + 1 \), leading to \( 5x = 8x + 9 \), which can be rewritten as \( 5x - 8x = 9 \). Therefore, we find \( -3x = 9 \) or \( x = -3 \). Now, substituting \( x = -3 \) back into the expression for \( y \): \( y = 4(-3) + 4 = -12 + 4 = -8 \). Thus, the solution to the system is \( (x, y) = (-3, -8) \).